2019
DOI: 10.1016/j.addbeh.2018.09.022
|View full text |Cite
|
Sign up to set email alerts
|

How do college students subjectively evaluate “blackouts”?

Abstract: Blackouts (i.e., alcohol induced memory impairment) are common among college student drinkers, and they are associated with several additional harms. However, alcohol consequences are not perceived universally as negative by the students who experience them, and little is known regarding students' specific thoughts and feelings about blackouts. We conducted a series of single-gender focus groups (8 groups; 5-8 per group; n=50, 56% female) with college student drinkers. Questions focused on: (a) their subjectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
14
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 15 publications
(21 reference statements)
5
14
1
Order By: Relevance
“…It is possible that these effects, or the other consequences demonstrated to cooccur with blackouts in this study (embarrassment, hangover), are mechanisms that help to explain effects of blackouts on both mood and event evaluations. Indeed, a prior qualitative study revealed that blackouts themselves are rated more negatively when they are accompanied by other negative consequences (Merrill et al., ); the same may be true for the overall drinking event.…”
Section: Discussionmentioning
confidence: 95%
“…It is possible that these effects, or the other consequences demonstrated to cooccur with blackouts in this study (embarrassment, hangover), are mechanisms that help to explain effects of blackouts on both mood and event evaluations. Indeed, a prior qualitative study revealed that blackouts themselves are rated more negatively when they are accompanied by other negative consequences (Merrill et al., ); the same may be true for the overall drinking event.…”
Section: Discussionmentioning
confidence: 95%
“…Prior work shows some undergraduates positively evaluate risky alcohol effects like cognitive impairments which could help explain why some CWDM drinkers might seek out blackout effects from alcohol (see also Ref. ). Having a positive view alcohol‐induced cognitive problems, a phenomenon typically experienced as aversive for drinkers , might constitute one of the characteristics that differentiate CWDM from other drinkers and might contribute to the established riskiness of this drinking motive .…”
Section: Discussionmentioning
confidence: 99%
“…Mentions of context alone without mention of effects on mood were not included in the final analysis given the focus of our study; however, mentions of context along with an impact on mood, cognitions, or behaviours were captured in our codes. Past experimental work about the impact of drinking context on alcohol ' s effects suggests that engaging in a distracting task might interact with alcohol to enhance its beneficial effects on mood . Future qualitative studies could contribute further to hypothesis‐generation about the impact of context on alcohol ' s effects on depression by asking about context for every story.…”
Section: Discussionmentioning
confidence: 99%
“…Although some drinkers assert that blackouts occur unintentionally (e.g., Wombacher et al, 2019), the current findings suggest that at least some drinkers can articulate intentions that translate into behavior. Our own qualitative research reveals that drinkers who experience blackouts endorse nuanced evaluations of the experience; while most report blackouts to be negative experiences, some describe them using neutral or even positive terms (Merrill et al, 2019). More specifically, this prior study showed that how a blackout is viewed may depend on the context in which it is experienced, with less negative evaluations reported when blackouts were expected to occur, and were experienced among familiar friends and/or in familiar locations.…”
Section: Discussionmentioning
confidence: 82%